(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
In 2012, the National University of Science and Technology (NUST) in Zimbabwe reviewed the University qualification entry cut-off points downwards in the Applied Mathematics Department. Following the review, there has been a worrisome and distinct change in student performance in first year mathematics courses. To explore the possible causes of the poor performance amongst students, a two-stage probability sampling technique was used to collect secondary data covering mainly admission entry level qualification for each student. A one-way Sir Ronald Fisher’s Analysis of Variance model (ANOVA) was used to explore the contribution of various hypothesised factors to performance in first year undergraduate courses. Mathematics grade at advance level and overall performance in all subjects done at Advanced level by a student have a significant influence on his or her first year pure Mathematics courses performance at NUST. We recommend that the Department should em-ploy remedial strategies to first year pure Mathematics courses if students with low scores in advance level mathematics are to be admitted. Instead of focusing on service courses with large classes only, the Department should prioritise allocating extra tutorial hours to pure Mathematics courses. Furthermore the effects of brain drain can- not be ignored, hence the University should find ways to curb or deal with the gap that the highly experienced staff who left, created.